Representation of Metaphor ‘FUTURE EVENTS ARE AHEAD’ in German Political Cartoons - Galina L. Denisova (RUDN Journal of Language Studies, Semiotics and Semantics)
The paper studies the actualization of the metaphor ‘FUTURE EVENTS ARE AHEAD’ in the German political cartoon as a polycode text. The author of the article finds out that images and situations, which the cartoonist uses for the purpose of its actualization, gravitate towards centers in the associative field of the concept WAY: movement by land, by water and in the air. Its actualization is realized through the taxonomical class exchange of participants in the translocation situation, which are an agent, destination or direction and initiator. As a result, the transposition in the area of temporal relations takes place. The analysis of cartoons allows the author discover transposition indications, which direct the addressee to correct decoding of caricaturist’s message. Transposition indications are (1) the taxonomical class exchange of the agent, namely: depicting the social wholeness as a character; incarnating an Abstract notion as a creature; representing the social wholeness as a transport facility; (2) the taxonomical class exchange of the destination or direction, exactly: indicating the event as an aim of movement; naming the direction with the name of a political leader; (3) the taxonomical class exchange or specification of the initiator, such as: depicting a political leader at the control stick of an airplane or at the helm of a ship; superposition of both images: a political leader and a transport facility. The paper notes that the metaphor under research forms the temporal structure of the message and takes place in the forming of its modality by means of detailing the picture.